Intervenciones de enfermería y su relación con la prevención de ulceras por presión en pacientes ingresados en unidad de cuidados intensivos del Hospital Alfredo Noboa Montenegro, Guaranda. Octubre 2024- mayo 2025. - Velasco Herrera, Gissela Fernanda (2025)
Pressure ulcers in the ICU are a challenge for nursing, as their prevention requires timely and effective interventions. Applying evidence-based strategies such as skin protection helps prevent them. The objective was to evaluate the effectiveness of nursing interventions and their relationship with pressure ulcer prevention in patients admitted to the intensive care unit of the Alfredo Noboa Montenegro Hospital, Guaranda. The methodology applied, depending on the level of study, was descriptive, time-based, cross-sectional, and retrospective, using an inductive, statistical, and analytical-synthetic method. Patients with medical records and nursing professionals responsible for their care were included. A predominance of patients aged 40 to 59 years (75%) was identified, with a higher frequency of women (65%). There was a predominance of patients who were hospitalized for more than four weeks (50%). They did not present with recurrent pressure ulcers (60%), while those affected had only one lesion (55%), located on the heels (50%) and of Grade II (55%). Regarding interventions, the healthcare provider performed repositioning every three hours (50%) and used anti-bedsore mattresses (58%). The Norton Scale was applied by all (100%). Staff reported moderate knowledge about prevention (61%) and in some cases delegated preventive interventions (48%). It is concluded that nursing interventions have contributed to reducing the incidence of pressure ulcers; however, variability in their application and the lack of clinical records limit a comprehensive risk assessment.